How to (re)write the History of Southern Italy in the Late Middle Ages? A research project about the ‘Textual Forms of the Power’ (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The paper presents a research project financed by the Italian Ministry (PRIN). The project assumes that it is not possible to renew the historiography about Southern Italy in late Middle Ages if we do not describe and study systematically some archival series kept in the Archivio di Stato of Naples, where you can find the administrative and fiscal documentation of the entire Kingdom. The focus is on the archival series, which are mere collections of 15th cent. documents and books; their relevance for the history of Southern Italy; the objectives and the scientific outcomes of the project; the project management. The PI aims to build a strictly integrated research group, including the officers of the Archivio di Stato of Naples, in orden to share every information and material during the project.
Keywords: Kingdom of Naples; Archives; Institutions; Diplomatics; Historiography; Project Management